Mirror Image or Molecular Mirage? Investigating Hormone Receptor Disconcordance in Breast Cancer Brain Metastases. - Qurat ul Ain Tariq; Eisha Abid Ali; Noman Ahmed; Saad-bin-Anis; Irfan Yousaf; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2025)
Breast cancer brain metastases (BCBM) are a significant clinical challenge, especially in aggressive subtypes like HER2-positive and triple-negative breast cancer. This review discusses hormone receptor discordance, it’s existence and contributing factors, the role of the bloodbrain barrier (BBB) in metastatic progression, and therapeutic modalities. While local treatments such as surgery and radiotherapy remain foundational, advances in systemic and immunotherapeutic approaches show promising potential. A deeper understanding of molecular mechanisms driving BCBM is essential to guide effective treatments and improve patient outcomes.